Maternal health care services utilization and associated factors among pregnant women in Kersa district, Jimma zone, Southwest Ethiopia - Tsedach Alemu Abebe; Gurmesa Tura Debelew (PLoS ONE, 2025)
Background Ethiopia has a high rate of maternal mortality, documented at 412 deaths per 100,000 live births in 2016. One of the most important interventions to reduce maternal death from pregnancy-related problems is the use of maternal health care services. However, the utilization of these services continues to be low in rural areas of Ethiopia. Therefore, this study aimed to assess the utilization and its associated factors of maternal health care services among pregnant women in rural areas of Kersa district, Jimma zone, Southwest Ethiopia. Methods A community-based cross-sectional study was conducted among 562 pregnant women in rural areas of Kersa District, Jimma Zone, Southwest Ethiopia, from October to December 2020. Cluster sampling was used to select study participants. The data was collected through face-to-face interviews using a pretested and structured questionnaire. The data was entered using Epi-data version 3.1 and SPSS version 21 was used for data cleaning, coding, labeling, and analysis. Bivariate and multivariable logistic regression analyses were performed to determine the association between dependent and independent variables. The significance level for analyses was set at p ≤ 0.05. Results Of the 562 women interviewed, 50.7% received at least one antenatal care (ANC) visit, more than two-thirds (70.5%) started ANC late, and only 2.8% completed ANC4 + visits. Nearly half (47.2%) of the women gave birth in a health facility. Women aged 20–29 years (AOR: 2.82; 95% CI: 1.27, 6.22) and 30–39 years (AOR: 1.86; 95% CI: 1.01, 3.42), women whose husbands were private employees (AOR: 2.23; 95% CI: 1.14, 4.38), women with good knowledge of pregnancy danger signs (AOR: 1.99; 95% CI: 1.34, 2.94), good road conditions (AOR: 2.63; 95% CI: 1.67, 4.13), and low transportation costs (AOR: 3.16; 95% CI: 1.64, 6.08) were positively associated with antenatal care attendance. Factors associated with institutional delivery service use were women aged 20–29 years (AOR: 3.47; 95% CI: 1.47, 8.17), private employee women (AOR: 5.46; 95% CI: 1.02, 29.17), women whose husbands were private employees (AOR: 2.38; 95% CI: 1.11, 5.11), households with a medium wealth index (AOR: 1.77; 95% CI: 1.05, 2.97), and rich households (AOR: 1.88; 95% CI: 1.09, 3.24), distance to health facility ≤ 1 hour (AOR: 4.95; 95% CI: 1.18, 20.76), and low transportation costs (AOR: 2.81; 95% CI: 1.51, 5.29). Conclusion Maternal healthcare service utilization among pregnant women in the study area was lower than national targets and international recommendations. Therefore, increasing women’s awareness of maternal healthcare services, addressing physical access to institutional delivery services, strengthening access to transportation such as making ambulance services more accessible, improving road conditions, and increasing household income would likely increase service utilization.